Synergistic Surface Modification for High‐Efficiency Perovskite Nanocrystal Light‐Emitting Diodes: Divalent Metal Ion Doping and Halide‐Based Ligand Passivation - Woo Hyeon Jeong; Seongbeom Lee; Hochan Song; Xinyu Shen; Hyuk Choi; Yejung Choi; Jonghee Yang; Jung Won Yoon; Zhongkai Yu; Jihoon Kim; Gyeong Eun Seok; Jeongjae Lee; et al. (Advanced Science, 2024)
Abstract Surface defects of metal halide perovskite nanocrystals (PNCs) substantially compromise the optoelectronic performances of the materials and devices via undesired charge recombination. However, those defects, mainly the vacancies, are structurally entangled with each other in the PNC lattice, necessitating a delicately designed strategy for effective passivation. Here, a synergistic metal ion doping and surface ligand exchange strategy is proposed to passivate the surface defects of CsPbBr3 PNCs with various divalent metal (e.g., Cd2+, Zn2+, and Hg2+) acetate salts and didodecyldimethylammonium (DDA+) via one‐step post‐treatment. The addition of metal acetate salts to PNCs is demonstrated to suppress the defect formation energy effectively via the ab initio calculations. The developed PNCs not only have near‐unity photoluminescence quantum yield and excellent stability but also show luminance of 1175 cd m−2, current efficiency of 65.48 cd A−1, external quantum efficiency of 20.79%, wavelength of 514 nm in optimized PNC light‐emitting diodes with Cd2+ passivator and DDA ligand. The “organic–inorganic” hybrid engineering approach is completely general and can be straightforwardly applied to any combination of quaternary ammonium ligands and source of metal, which will be useful in PNC‐based optoelectronic devices such as solar cells, photodetectors, and transistors.